Cryo-electron microscopy reconstruction of a poliovirus-receptor-membrane complex. - Bubeck, D; Filman, D; Hogle, J (2005)
To study non-enveloped virus cell entry, a versatile in vitro model system was developed in which liposomes containing nickel-chelating lipids were decorated with His-tagged poliovirus receptors and bound to virus. This system provides an exciting opportunity for structural characterization of the early steps in cell entry in the context of a membrane. Here we report the three-dimensional structure of a poliovirus-receptor-membrane complex solved by cryo-electron microscopy (cryo-EM) at a resolution of 32 A. Methods were developed to establish the symmetry of the complex objectively. This reconstruction demonstrates that receptor binding brings a viral five-fold axis close to the membrane. Density is clearly defined for the icosahedral virus, for receptors (including known glycosylation sites) and for the membrane bilayer. Apparent perturbations of the bilayer close to the viral five-fold axis may function in subsequent steps of cell entry.